CREATIVE THINKING ABILITIES OF PROSPECTIVE MATHEMATICS TEACHERS IN SOLVING OPEN-ENDED TRIGONOMETRY PROBLEM - Erisca Lusy Rusdianti; Hendro Permadi; Sisworo Sisworo (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
The current technological developments require students to have creative thinking skills. One of the four thinking skills needed in the 21st century is creative thinking skills which is still lacking in students. The purpose of this study was to describe prospective mathematics teachers’ creative thinking skills in solving open-ended trigonometry problems. This research is descriptive qualitative research. This study involved 40 prospective mathematics teachers who were then reduced to four subjects based on high and medium mathematical abilities which were studied in more depth in solving open-ended trigonometry problems. The research instruments used in this study were the researcher, interview guide, and open-ended trigonometry questions. The results of collegers work were analyzed based on aspects and levels of creative thinking skills. In this study, the data analysis phase includes data reduction, data presentation, and conclusion. Then triangulated the data in describing the results of the study. The results of this study are that first colleger with high mathematical abilities meet the aspects of fluency and novelty and the second fulfills the aspects of fluency and flexibility. First colleger with medium abilities fulfill the flexibility aspect and the second fulfills the novelty aspect. So, it can be concluded that collegers with high and medium mathematical abilities were solving open-ended trigonometry problems have a creative level and quite creative.